A Guide to Professional Doctorates in Business and Management - Anderson, Lisa 1950- (SAGE Publications, 2015)
This practical guide is designed for students undertaking professional doctorates in business and management including DBAs, and addresses a number of key issues faced by supervisors and students, in particular, how they differ from a PhD and the different skills and approach required to succeed